Hubungan Konsep Diri dengan Penerimaan Diri Siswa SMA Negeri 7 Padang - Fella Hanna Neisha; Zikra Zikra (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research was motivated by the low self-acceptance of students at SMA Negeri 7 Padang. Many factors influence self-acceptance, one of which is self-concept. The self-concept of students at SMA Negeri 7 Padang also experiences problems. Further research was conducted regarding the relationship between self-concept and students' self-acceptance at SMA Negeri 7 Padang. The aims of this research are: (1) analyzing students' self-concept; (2) analyzing students' self-acceptance; (3) examine the relationship between self-concept and students' self-acceptance at SMA Negeri 7 Padang. This research uses quantitative methods with a descriptive approach. The sample in this study was 273 students at SMA Negeri 7 Padang who were selected using the starified random sampling technique. Data was obtained using a valid and reliable self-concept and self-acceptance questionnaire. Data processing is carried out by calculating product moment correlation. The results of the research show that the self-concept of SMA Negeri 7 Padang students is in the good category (67.03%), the self-acceptance of SMA Negeri 7 Padang students is in the good category (60.81%) and there is a significant relationship between self-concept and self-acceptance with the coefficient (0.349).